Biopolítica, gripe a (H1N1) e mídia: o que pode um porco? - Corrêa, Guilherme (2012)
This study aimed to analyze how biopolitics encompasses the dis-media courses in a newspaper circulating in the central region of Rio Grande do Sul on Influenza A (H1N1), seeking to make visible how the institutional and discursive practices and are cross the subjects. As specific objectives, we aim to identify, in the symbolic forms of the newspaper, the ways in which population health can become the target of a power over life, and recognize the different elements disciplinary power bodies emphasized the symbolic forms and check discursive elements present in symbolic forms that may be contributing to make living biotechnologies. Initially a theoretical review of the main references on Sovereignty, Biopower, Discipline, and Biopolitics Biotechnologies. Following were recovered information about the development of epidemiology as a science is responsible for monitoring the health of populations especially in large cities, through different paradigms regarding the disease and its possible triggering factors, culminating in the development of modern epidemiology . Still follows a genealogy research concerning the influenza virus and its spread across the globe for about 2000 years, emphasizing the H1N1 viral strain. The following parts deal with smallpox vaccination in 1904 and vaccination of Pandemic Influenza A (H1N1) in 2009, the means of mass communication. In the final part presents the analysis of the reports, noting biopolitics in general and its consequences regarding the disciplining of bodies, production of knowledgepower, a standard society, pharmaceuticals and medicalization. From a genealogical perspective of historic, aimed at understanding the conditions that enable the emergence and permanence of discursive practices, we analyzed a total of 291 articles published during the month of July 2009, a period considered critical due to the number of deaths registers resulting from the pandemic of influenza A (H1N1). As a result of research, can be observed the influence of mass media and the symbolic elites have on the subject due to the constructions of symbolic material transmitted by the media, which ultimately have an effect not only on the bodies of the subjects, but the dynamics of populations.